Text Message Routing System for Chat-Based Applications - Angelo, Breno U. de; Zanetti, Guilherme G.; Souza, Alberto F. De; Badue, Claudine; Jacobsen, Abner G.; Oliveira-Santos, Thiago (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2026: Anais do XXII Simpósio Brasileiro de Sistemas de Informação, 2026)
Research Context: The integration of Large Language Models (LLMs) into banking customer service promises enhanced engagement but faces a trilemma of prohibitive operational costs, stochastic inaccuracy (hallucinations), and strict safety requirements. In the Brazilian financial sector, where inaccuracies can lead to direct financial harm, relying solely on monolithic LLMs is economically unsustainable and operationally risky. Practical Problem: Financial institutions struggle with the ”inference cost trap,” where token-based pricing scales linearly with usage, and the risk of hallucinations—where models generate plausible but incorrect responses for unfamiliar queries. Proposed Solution: This study validates a semantic routing architecture that functions as an intelligent decision layer, classifying user intent into four categories (Relevant, Unrelated, Chitchat, Spam) to route queries to cost-effective handlers. Five classification paradigms were benchmarked: Zero-shot GPT, Few-shot GPT, QLoRA fine-tuned GPT, Embedding Similarity Search, and BERT-based neural models. Related IS Theory: The research builds upon Task-Technology Fit (TTF) theory and contributes to the Green IS agenda by validating energy-efficient architectures. Research Method: A balanced dataset of 6,760 messages, curated from SMS spam data, SQuAD questions, private chats, and banking FAQs, was used to evaluate accuracy, resource usage, and cost. Summary of Results: Embedding Similarity (98.52%) and BERT-based models (98.96%) achieved superior accuracy compared to Zero-shot GPT (53.78%) and matched the performance of Fine-tuned GPT (97.93%). Crucially, the embedding approach reduced operational costs by 96% (from US$18.10 to US$0.32 per million requests) and slashed memory consumption from 6.52 GB to 1.04 GB. Contributions and Impact to IS Area: The study contributes a validated pattern for Frugal AI in Portuguese, demonstrating that open-source embedding models can effectively govern LLMs. This approach mitigates hallucination risks, reduces dependency on foreign APIs, and aligns with sustainable computing principles.